Preoperative anxiety management in children. Benefits of humanoid robots: an experimental study - Ilaria Franconi; Andrea Faragalli; Giulia Palego; Samuele Canonici; Ludovica Gatti; Alessandro Simonini; Edoardo Bindi; Edoardo Bindi; Giovanni Cobellis; Giovanni Cobellis; Flavia Carle (Frontiers in Surgery, 2023)
ObjectiveThe purpose of this study was to determine whether the use of a humanoid robot (Estrabot) could reduce preoperative anxiety levels in children.MethodsAn experimental study was conducted at Azienda Ospedaliero Universitaria delle Marche Hospital, involving the Pediatric Surgery ward and the Operating Room (OR). Patients aged between 2 and 14 years who underwent minor surgery were included. The Instruments used were the Children's Emotional Manifestation Scale to evaluate anxiety levels, and Estrabot, a humanoid robot that interacts with people. Medical records between April and May 2023 were analyzed and the data was anonymous. The level of anxiety is extrapolated in Pediatric Surgery during the administration of oral pre-medication, and in the Operating Room, during the induction of anesthesia. Patients were divided into an intervention group treated with Estrabot, and a control group without a robot.ResultsThe population consists of 60 patients (86.7% male) with a median (IQR) age of 6 (4–8) years. The median (IQR) anxiety score during premedication was 7 (5–11), while the median (IQR) anxiety score during anesthesia was 6 (5–10). A significantly lower level of anxiety was reported in the Estrabot group. Patients in the Estrabot group had significantly lower anxiety levels in different age groups.ConclusionA humanoid robot can reduce preoperative anxiety levels in children during premedication and the induction of anesthesia.